How Instagram Drives Promotion for Melasti Beach: A Study on its Effectiveness - Tanara, Casey; Tirtawati, Ni Made; Agustini, Ni Putu Oka (PT FORMOSA CENDEKIA GLOBAL, 2024)
Melasti Beach is one of the tourist attractions that uses social media, especially Instagram as a promotional medium, therefore it is very important to know the effectiveness of social media in promoting a tourist attraction. The purpose of this study is to determine the effectiveness of social media Instagram as a promotional media at Melasti Beach Ungasan. The data sources used are primary and secondary. Respondents in this study totaled 100 respondents who interacted with the Instagram account @melastibeach.official and had visited Melasti Beach. The data analysis technique is descriptive statistical analysis with a quantitative approach in terms of the AIDA analysis model. The results of this study show that the total value of Attention dimension is 1755, Interest dimension is 1743, Desire dimension is 1742 and the Action dimension is 1763. The total expectation value for each dimension has the same value 2000. The results of the percentage effectiveness of Attention dimension is 88% which graphic content from Instagram @melastibeach.official can attract the attention of tourists, Interest dimension is 87% which tourists are interested in knowing more information about the tourist attractions displayed Instagram @melastibeach.official and Desire dimension’s is 87% which make Instagram content @melastibeach.official as reference material to visit and Action dimension has a percentage result of 88% where tourists decide to take a trip to the Melasti Beach after seeing the Instagram profile @melastibeach.official. From the percentage results in each dimension at a special level, @melastibeach.official’s Instagram is effective as a promotional medium at the Melasti Beach.